Nanocomposites, nanophotonics, nanobiotechnology, and applications : selected proceedings of the second FP7 Conference and International Summer School Nanotechnology: From Fundamental Research to Innovations, August 25-September 1, 2013, Bukovel, Ukraine /: selected proceedings of the second FP7 Conference and International Summer School Nanotechnology: From Fundamental Research to Innovations, August 25-September 1, 2013, Bukovel, Ukraine. (2015) - Unknown
No abstract available